Tracing Accountability: The Role of Due Diligence in Addressing Business-Related Human Rights Violations - Khushbakht Qaiser; Hasani Mohd Ali; Rohaida Nordin; Zarfishan Qaiser (Journal of Indonesian Legal Studies, 2026)
This article explores the extent to which a corporation can avoid or eliminate the legal liability for a breach of the duty of care following a human rights catastrophe in the business context by proving that it adhered to the United Nations Guiding Principles on Business and Human Rights (UNGPs) and the rigorous exercise of Human Rights Due Diligence (HRDD). Using a doctrinal legal methodology, it examines the interplay between the concepts of HRDD and core concepts of negligence; the concept of duty of care, foreseeability and breach and causation based on emerging case law and regulatory developments on corporate responsibility. The article argues that although compliance with the UNGPs cannot be used as an automatic defence to civil claims, robust and well-documented HRDD is a significant factor in how courts weigh up what harms were reasonably foreseeable and whether the corporate defendant exercised the standard of care required by law. On the other hands poorly implemented or superficial HRDD would strengthen findings of breach by demonstrating that the company knew but condoned serious risks. By re-conceptualizing HRDD as an evidentiary and normative standard in the field of negligence law, the article has suggested a methodical model of assessing corporate responsibility in business-related human rights violations.